The Use of Educational Stickers as Indonesian Language Learning Campaign Media in the Era of Multilingual Communication - Yulandari, Esti; Saddhono, Kundharu; Eko Wardani, Nugraheni (JUPE : Jurnal Pendidikan Mandala, 2024)
Technological advances have caused numerous changes in every aspect of human life, including the languages used in communication. Indonesia is one of the countries with a multitude of languages, so in general, the Indonesian population communicates in more than one language. However, Indonesian serves as the national language that unites the nation amid the various regional and foreign languages that exist. The position of the Indonesian language should be prioritized over others because it is used as the national language and for communication in public spaces. However, over time, the existence of the Indonesian language has begun to erode. To preserve its existence, a campaign for the Indonesian language is necessary, and this can be achieved through the creation of educational stickers using Canva as a medium. This research employs a qualitative descriptive method. The production of stickers through Canva is expected to be one of the efforts to preserve the Indonesian language and its status as the national language for communication in public spaces.